Determinants of Romanian International Migrants' Remittances - Zizi Goschin; Monica Roman; Aura Popa (European Regional Science Association (ERSA), 2011)
In the past few years, there has been a renewed interest in remittances of international migrants, as their strong recent increase shed more light on the effects at both micro and macro level. The remittances not only contribute to the well-being of the receiving households, but are also a large source of external financing, second only to FDI. The remittances are particularly important for Romania as in 2010 it was on the 5th place in the European top of emigration countries and on the 4th place as remittance recipient country. Therefore the determinants of remittance behavior need to be better understood. Following increasing interest and significant public debate on migration in Romania, our paper examines the significance of selected economic and demographic factors associated with the remittance behavior of Romanian international migrants, as characterized by the propensity to remit and the amount remitted. In particular we address the question of the role played by the geographic distance, as potentially affecting the immigrants' ties with their homeland and consequently the remittance decisions. Our present work builds on a recent source of data on immigrant cohort resulting from an online survey conducted during August-December 2010. Respondents were asked questions on a variety of topics including income, employment, remittances, regions of origin and destination, graduated studies both in Romania and in emigration country, length of migration and intention to return to Romania. The final database consisted of 1514 Romanian immigrants from 55 destination countries. We developed several multivariate models to study the determinants of remittances by employing regression analysis. Among the main findings is that the geographic distance is not related to the remittances. Although contrasting with the existing literature, this result can be explained by factors such as modern instant communication and fast travel supporting very strong and resilient transnational links despite geographic distance.
Keywords: 330